Phonological awareness and lexical processes in reading in five year old kindergarten and second grade students from a school in the City of Lima - Cannock, Jennifer I. (2014)
The aim of this research was to establish the relationship between phonological awareness and lexical processes in reading. This study was correlational, longitudinal and its design was not experimental. Thirty six students from a public school in the city of Lima were assessed in two stages: kinder and 2nd grade. The Phonological Awareness Assessment Test - PECO and the Lexical Processes subtests - PROLEC-R were used, both in adapted versions. The results showed that there is no significant relationship between phonological awareness and lexical processes in reading. However, there is a significant relationship between syllable identification task and word reading subtest in speed and reading skills indexes. A significant relationship between syllable identification task and pseudowords reading in reading skills index was found. Also, a significant relationship between syllabic omission task and pseudoword reading in reading skills index was evidenced.